Quipper Application for Teaching Descriptive Text: Concurrent Mixed Methods Study at MAN 3 Banyuwangi - Aribah, Nila Husnul (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the effectiveness of using the Quipper application in improving the comprehension of Descriptive Text among Grade X3 students at MAN 3 Banyuwangi. The study employed a Mixed Methods Concurrent approach, with quantitative data collected from pretest and posttest results, and qualitative data gathered through interviews and observations. The findings indicate that the use of the Quipper application had a significant impact on students' understanding. The average accuracy of students increased from 47% in the pretest to 63% in the posttest, with notable improvement across nearly all question categories. Quipper's interactive features, such as video lessons and quizzes with immediate feedback, proved effective in helping students grasp text structure, grammar, and vocabulary in Descriptive Text. However, some students continued to face challenges in technical aspects, such as grammar, which require additional guidance from teachers. This study concludes that combining educational technology like Quipper with conventional teaching methods is an effective strategy to enhance student learning outcomes.